2018
DOI: 10.1007/s12020-017-1510-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone in pre-menopausal females after ablative radioiodine treatment for differentiated thyroid cancer

Abstract: AMH should replace FSH in the evaluation of gonadal reserve in pre-menopausal thyroid cancer women. At present, age is the only predictor of AMH levels. About one out of two women with a history of thyroid cancer suffers from menstrual dysregulation, but infertility must be considered a low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 36 publications
4
25
2
Order By: Relevance
“…AMH levels were only slightly, and not significantly, lower in those patients who had undergone RAI [15]. In both studies, the interval between thyroidectomy and RAI administration and AMH sample collection was of several months: more than 36 months in the Acibucu et al study [14] and 5 years on average in our study [15]. Recently, Yaish et al [16] and Evranos et al [17] designed similar studies in which AMH was evaluated before and 3-12 months after RAI administration in DTC females.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…AMH levels were only slightly, and not significantly, lower in those patients who had undergone RAI [15]. In both studies, the interval between thyroidectomy and RAI administration and AMH sample collection was of several months: more than 36 months in the Acibucu et al study [14] and 5 years on average in our study [15]. Recently, Yaish et al [16] and Evranos et al [17] designed similar studies in which AMH was evaluated before and 3-12 months after RAI administration in DTC females.…”
Section: Introductionmentioning
confidence: 74%
“…First, in 45 women aged 36 years on average who had been exposed to RAI, Acibucu et al [14] reported lower AMH levels than in 40 healthy body mass index (BMI)-and agematched females. We [15] measured AMH levels in 34 pre-menopausal women treated with RAI for DTC and compared these with those of 23 age-matched women with DTC who had not received RAI therapy. AMH levels were only slightly, and not significantly, lower in those patients who had undergone RAI [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations